Pengaruh Lingkungan Bisnis terhadap Kinerja Bisnis Perusahaan melalui Strategi Kompetitif dan Strategi Manufaktur sebagai Mediator: Studi pada Perusahaan Menengah dan Besar di Indonesia - Martono, Cyrillus; Ellitan, Lena (Kajian Manajemen dan Bisnis, 2011)
This research is conducted to test whether a conceptual model of manufacturing strategy is relevant when applied in different research settings among medium and large manufacturing companies in Indonesia. The study generally indicates that environmental uncertainty has no significant effect on the choice of competitive strategy and manufacturing strategy among medium and large companies.